A case of focal eventration of left hemidiaphragm with transthoracic left kidney confused with a traumatic diaphragmatic hernia - Hassan, Radhiana; Mohd Yusof, Mubarak (Malaysian Medical Associations, 2011)
Focal eventration of the diaphragm with transthoracic kidney is a very rare condition. It is usually asymptomatic and often revealed as an incidental finding on imaging studies. We presented a case of previously undiagnosed focal eventration of left hemidiaphragm with transthoracic left kidney confused with traumatic diaphragmatic hernia. Differentiation of these two conditions is important as each were managed differently. A traumatic diaphragmatic hernia needs early surgical intervention whereas no treatment was required for focal diaphragmatic eventration in most cases. Diagnostic laparoscopy confirmed the findings in this case and the patient was managed conservatively.